Peran Masyarakat Adat Kelurahan Sedinginan Kecamatan Tanah Putih Kabupaten Rokan Hilir dalam Penyelesaian Sengketa Perkawinan - Asrul Ariadi; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesian nation is a nation consisting of various tribes. The hundreds, so that itslegal culture and also varied. Such legal in Indonesia called Customary Law, marriagedisputes that occur in indigenous village land sedinginan white districts downstream districtsrokan completed by ninik Mamak. Based on the description above, the writer interested inconducting research with the title "The Role of Indigenous Village districts Sedinginan whiteground rokan districts downstream in Marriage Dispute Resolution".Based on the purpose of this study, the authors formulate three objectives, namely:first, to determine the position of ninik mamak in marriage law on indigenous peoples'villages sedinginan districts white ground district rokan downstream, second, to determinethe role ninik mamak in dispute settlement marriage of the tribal community traditionalvillage district sedinginan white ground rokan districts downstream, third, to determine therole ninik mamak in different marital dispute resolution terms in the indigenous villagedistricts sedinginan white ground rokan districts downstream.This type of research is to conduct research Sociological directly to the location of theresearch in this case is Sedinginan Tanah Putih Village Rokan Hilir. The data used in thisresearch is primary data, secondary data, and the data tertiary. Data collection techniques inthis research with interviews, questionnaires, and literature study. The analysis of the data inthis research is qualitative analysis using deductive method namely conclusion of the matterthe general to things - things that are special.Based on the results of this study concluded. First, the position ninik mamak inmarriage law on indigenous peoples' land districts sedinginan white villages rokandownstream district is already declining and is ignored by most people. Secondly, a marriagedispute resolution terms in the indigenous village districts sedinginan white ground is themediation that the mediator is ninik mamak. Third, different marital dispute resolution termsin the indigenous village districts sedinginan white ground rokan downstream district isnegotiating by each - each of the ninik Mamak. For that is expected ninik mamak makingassociation in any given time with the community not to ignore the stages of marriage shouldinvolve ninik Mamak in it as well as the enhanced capability as a mediator in mediating asolution to the problems in the household experienced by children nephew and foster betterrelationship again with ninik mamak other parts to make it easier ninik Mamak negotiatedsettlement of the problem in the household experienced by children nephew.Keywords: Role - Indigenous Peoples - Marital Dispute